Atmospheric circulation influence on temperature and precipitation individual and compound daily extreme events: Spatial variability and trends over southern South America - Olmo, Matías Ezequiel (2020)
Southern South America (SSA) is an extended region where temperature and precipitation daily extreme events have several impacts on the different socio-economic activities. In this work, their individual and compound occurrence over SSA and their association with atmospheric circulation were studied during 1979–2015, using meteorological stations and the CPC gridded dataset. Results were generally in good agreement between both datasets. The occurrence of a warm night (minimum temperature exceeding the 90th percentile) or a cold day (maximum temperature below the 10th percentile) significantly increases the probability of heavy precipitation (daily precipitation exceeding the 75th percentile) in southern Chile and southeastern South America. These compound events were regionally conditioned by specific circulation types. In addition, both individual and compound extremes showed trends in the different sub-regions. On one hand, heavy precipitation exhibited a significant increase over central-eastern Argentina and Uruguay, northeastern Argentina and southern Brazil during the warm season, and a significant decrease in central and southern Chile during the cold season. On the other hand, warm (cold) extremes generally presented significant upward (downward) trends. Compound events showed significant positive trends for selected regions, in some cases coincident with trends in individual extremes. Changes in the frequency of circulation patterns were found to partly influence some of these trends, like the increases in heavy precipitation and warm extremes during the warm season.